What do integrated STEM projects look like in middle school and high school classrooms? A systematic literature review of empirical studies of iSTEM projects - Felicity I. McLure; Kok-Sing Tang; P. John Williams (SpringerOpen, 2022)
Abstract The past 20 years has seen a growing focus on the integration of Science, Technology, Engineering and Mathematics (iSTEM) disciplines in schools to provide students with authentic experiences in solving real-world problems. A frequently stated aim for iSTEM projects has been increasing engagement and interest in pursuing STEM subjects in senior high school and tertiary studies. In order to better understand the iSTEM projects' landscape in school classes, this systematic literature review analysed empirical studies of integrated STEM projects carried out in secondary schools to answer the following questions: What are the characteristics of the projects described and to what extent do these projects reflect characteristics of effective STEM projects; and to what extent does research into iSTEM projects in classrooms investigate specific methods of integration of STEM domains? Thirty-five peer-reviewed publications were identified from database searches that met the following inclusion criteria: (a) integrating two or more of the STEM areas, (b) middle/high school education and (c) explicitly describing the research intervention. The review revealed a diversity of iSTEM approaches in the literature, with Engineering and Science, particularly Physics, the most commonly integrated fields. Concerns are raised about the degree to which projects are relevant to students and their context and address the diversity found within student cohorts. A gap was found in the literature in detailing how teachers and students enact integration of STEM skills in these projects.